Meningkatkan Stabilitas Tanah dengan Penggunaan Bahan Additif Tx – 300 Pada Jalan Raya Wates – Kediri - Wahyu Agung Nugroho; Sigit Winarto; Agata Iwan Candra; Fajar Romadhon (Kadiri University, 2021)
In ensuring the quality of infrastructure, the role of land as support for buildings is very crucial. Road transportation infrastructure located in Sumberagung Village, Wates Subdistrict, Kediri Regency, has often experienced estimated damage due to unsuitable soil surface layer specifications. On this occasion, the authors conducted a research study on soil characteristics at the location. They carried out experiments to repair damage to the soil surface layer using a combination of additive TX - 300 media in the amount of 5%, 10%, and 15%. The method used was to test soil particles at the location and perform Index Plastic and Proctor tests to measure soil improvement efforts using TX-300 additives. The study results stated that the soil in the area had the criteria of GP (poorly graded gravel) and SP (poorly graded sand). On the USCS theory and the Montmorillonite category in the ASTM classification. The soil plastic index value was 19.37%. The dry volume weight (É£d) of the Proctor after being converted to the importance of the contents was 3.61 gr/cm3. The Plastic Index value increased to 34.44% after the additive TX-300 combinations.Â In the 10% combination, the test value (É£d) of Proctor increased to 4.59 gr/cm3.